Selection biases in elite youth handball: early maturation compensates for younger relative age - Thieschäfer, Lutz; Schorer, Jörg; Beppler, Jochen; Büsch, Dirk (Frontiers in Sports and Active Living, 2025)
Talent selections in youth sports are frequently biased regarding the maturation and relative age of the players, with preference given to more mature and relatively older players. It thus can be hypothesized that relatively younger players born at the end of the selection year must mature earlier to compensate for this disadvantage. Hence, this study investigated maturation, relative age, and their association in the talent selection of German youth handball players. A secondary data analysis within an ex post facto design was conducted to examine the birth quarter distributions and maturation parameters of 2,259 female U15 players and 2,340 male U16 players. Practically significant maturation bias was detected in male players, who matured almost one year earlier than common German boys (g = −1.67). This was not evident in female players. Relative age selection biases were observed in female (פ‎ = .16) and male (פ‎ = .20) players. An analysis of maturation timing across birth quarters revealed that relatively younger players born later in the selection year mature earlier than their relatively older peers in both female (g = 0.99) and male players (g = 0.56), thereby partially offsetting relative age disadvantages. Consequently, it may be crucial for relatively younger players to be early-maturing to increase selection odds. Considering the evidence indicating the presence of both maturation and relative age selection biases, it seems prudent to acknowledge the significant impact that these can have on talent selection and development in German youth handball. The development of solutions is currently underway in collaboration with the regional and national handball federations.